2020
DOI: 10.1556/030.2020.01059
|View full text |Cite
|
Sign up to set email alerts
|

Human coronavirus OC43 and other respiratory viruses from acute respiratory infections of Egyptian children

Abstract: Respiratory infections have a significant impact on health worldwide. Viruses are major causes of acute respiratory infections among children. Limited information regarding its prevalence in Egypt is available. This study investigated prevalence of 10 respiratory viruses; Adenovirus, influenza A, B, respiratory syncytial virus (RSV), Parainfluenza virus (PIV)type 1-4, enterovirus, and human coronavirus OC43 (HCoV-OC43) among children in Alexandria, Egypt presenting with acute lower respiratory tract infections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…Coronavirus was detected in other studies. In Egypt, Naga et al ( 2020 ) reported the presence of 3 cases, and in Saudi Arabia, Al-Ayed et al ( 2014 ) found positive samples for NL63 and OC43 in 3.7% of their cases.…”
Section: Discussionmentioning
confidence: 99%
“…Coronavirus was detected in other studies. In Egypt, Naga et al ( 2020 ) reported the presence of 3 cases, and in Saudi Arabia, Al-Ayed et al ( 2014 ) found positive samples for NL63 and OC43 in 3.7% of their cases.…”
Section: Discussionmentioning
confidence: 99%